PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, IKLIM ORGANISASI DAN STRES KERJA TERHADAP KEPUASAN KERJA PERAWAT DI RUMAH SAKIT JIWA DAERAH SURAKARTA - Rahayu Triastity, Nuning Purwanti & (Universitas Slamet Riyadi, 2017)
This research is conducted to analysis the effect of: Transformationalleadership style to the satisfaction work nurse, organisastion climate to thesatisfaction work nurse, work stress to the satisfaction work nurse, whichvariable which most dominant influence the satisfaction work nurse.Thepopulation is entire nurse at Rumah Sakit Jiwa Daerah (RSJD) Surakarta asmany as 225 nurses. The sample is taking by purposive sampling, as manyas 80 nurses. The technique of gathering the data is using questionerthrough validity test and reliability test. The analysis technique uses doubleregression with classical assumption.The conclusion of the research:Transformational leadership style have significant influence to satisfactionwork nurse. Organizational climate have significant influence to satisfactionwork nurse. Work stres have significant influence to satisfaction work nurse.Transformational leadership style have dominant significant influence tosatisfaction work nurse at RSJD Surakarta.Keywords: transformational leadership style, organizational climate, workstress, satisfaction work nurse